منهج مركز التطويري لتدريس اللغة الأجنبية بالمدرسة الثانوية "جاء الحق" في تحسين مهارة اللغة العربية - Muhammad Hidayaturrahman (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2019)
The purpose in this research is to determine the curriculum of the developmental center of foreign language teaching in high school came right, the curriculum has met the elements in the curriculum or not. It is inspired by the first curriculum making, the objectives of the curriculum and the content or subjects and the process of teaching and evaluation. The type of research in this research is field research with the qualitative approach of using the curriculum made at the Development Center for Teaching Foreign Language. Data collection will be done with observation, interview and documentation. Data analysis uses four phases: data collection, data limit, data presentation, and extraction. The results of the research is to analyze the curriculum development center for teaching foreign language in improving the skill of the Arabic language, and show that the curriculum used to meet the elements of the curriculum is the objectives of the curriculum and content or subjects and the process of teaching and evaluation. The teaching process is still not perfect because of the impossibility of time and the curriculum being taught is different. The barriers are the time of assembly because each one has a busy life irregularities between the foundation and the wishes of the coach. The supporting factors are the support of the curriculum heavily by the Foundation as a trainer for students to speak foreign (Arabic) fluently. Therefore, the curriculum is not fully maximized.